2013
DOI: 10.1111/ibi.12100
|View full text |Cite
|
Sign up to set email alerts
|

Annual survival of adult Atlantic Puffins Fratercula arctica is positively correlated with Herring Clupea harengus availability

Abstract: Atlantic Herring is a keystone species in several marine ecosystems, supporting intensive fisheries as well as many predators including seabirds. Biomass of this stock in eastern North America has declined considerably in recent years, potentially putting at risk populations of its predators. Although adult survival in seabirds is considered robust to moderate changes in food availability, it is also the life‐history component most critical to sustaining populations of long‐lived birds. To investigate the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…in Atlantic puffins Fratercula arctica and herring abundance (Breton and Diamond 2014), Brandt's cormorant Phalacrocorax penicillatus and rockfish Sebastes spp. (Nur and Sydeman 1999) and many others (Furness 2007).…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…in Atlantic puffins Fratercula arctica and herring abundance (Breton and Diamond 2014), Brandt's cormorant Phalacrocorax penicillatus and rockfish Sebastes spp. (Nur and Sydeman 1999) and many others (Furness 2007).…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…Estimates of Herring Gull numbers on Kent Island since 1940 (Ronconi and Wong 2003) indicate that the population has declined at an average rate of 111 breeding pairs (1.33%) per year since 1967 (a 64% decline). In the lower Bay of Fundy, Atlantic Herring is a critical food resource for many seabirds (Diamond and Devlin 2003, Ronconi et al 2010, Breton and Diamond 2014 and marine mammals (Overholtz and Link 2007). Herring Gull diet on Kent Island from late May to early July consists primarily of herring, mackerel, and, to a lesser extent, crab (Steenweg et al 2011), though it is not known whether the herring in the diet comes from natural prey sources or discarded lobster bait.…”
Section: Discussionmentioning
confidence: 99%
“…For birds breeding on the nearby Machias Seal Island, it has been suggested that the decline in herring availability has contributed to the decline in adult survival of Atlantic Puffins (Fratercula arctica; Breton and Diamond 2014) and that the quality of herring prey, e.g., energy density in the form of fat content, was also important to the breeding success of terns (Sterna spp. ; Diamond and Devlin 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although these data may not match conclusions from landings or bottom-trawl surveys, we encourage fisheries scientists to consider the biological relevance of these data sources, especially as they support trends observed in diet of herring predators. Seabirds are often overlooked in studies of herring predators because the relative proportion of the herring stock that they consume is much less than that of groundfish or marine mammals (NEFSC 2012), but herring can be integral to seabird reproductive success and survival (Massias and Becker 1990;Durant et al 2003;Breton and Diamond 2014), emphasizing the need for EBFM in this ecosystem. Correlations between mobile-gear landings and the data of common terns, puffins, and razorbills suggest that these seabirds select herring preferentially, further supporting the need for cautious herring management.…”
Section: Seabirds As Herring Indicatorsmentioning
confidence: 99%
“…Among many examples are sandeels (or sandlance; Ammodytes spp.) in the North Sea (Monaghan et al 1989;Frederiksen et al 2008;Cook et al 2014) and Gulf of Alaska Suryan et al 2006); capelin (Mallotus villosus) around Newfoundland and Labrador (Montevecchi and Myers 1996;Regehr and Montevecchi 1997), the Barents Sea (Barrett and Furness 1990), and Gulf of Alaska ; anchovy and sardines in the Benguela Current (Crawford et al 2008; Green et al 2015), the Humboldt Current (Duffy 1983), and California Current (Mills et al 2007;Sydeman et al 2009; Thompson et al 2012); and Atlantic herring in Iceland, Norway (Anker-Nilssen 1987), and the Gulf of Maine (Diamond and Devlin 2003;Breton and Diamond 2014).…”
Section: Introductionmentioning
confidence: 99%